2018
DOI: 10.21608/jpp.2018.36367
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Resistance as Function of Physical and Chemical Properties of Selected Faba Bean Promising Lines against Callosobruchus maculatus Post Harvest

Abstract: The present investigation was conducted during two growing seasons 2015/2016 and 2016/2017 at Sakha Agricultural Research Station farm, in order to evaluate thirteen faba bean genotypes to physical and chemical properties against insects attack to faba bean seed from breeding program, under early and late sowing dates (mid-October and mid-November, respectively) comparing with three varieties were assessed to study their response to infestation with Cowpea weevil Callosobruchus maculatus post-harvest through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…maculatus , while the least susceptible variety was Giza 716 in free- choice method . These results are in agreement with the findings of El- Rodeny et al (2018) on other broad bean genotype who indicated that Sakha 3 genotype of broad bean was tolerant to the infestation with C . maculatus in storage since it had low number of progeny and short developmental period.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…maculatus , while the least susceptible variety was Giza 716 in free- choice method . These results are in agreement with the findings of El- Rodeny et al (2018) on other broad bean genotype who indicated that Sakha 3 genotype of broad bean was tolerant to the infestation with C . maculatus in storage since it had low number of progeny and short developmental period.…”
Section: Discussionsupporting
confidence: 93%
“…maculate , while the least susceptible one was Giza 716 in free- choice method . These results partially agreed with that recorded by El- Rodeny et al (2018) who found that the broad bean line 2 and Sakha 3 were tolerant against C . maculatus in storage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The quality of host plants can influence the life history, population growth, oviposition preference, and feeding performance of insect pests [ 22 , 23 ]. Plant physicochemical properties including primary and secondary metabolites, as well as trichome density, tissue hardness, and moisture content can determine the oviposition behavior and population performance of insect pests [ 24 , 25 , 26 , 27 , 28 ]. Therefore, study of these parameters, as resistance indices, could be useful in the identification of resistant cultivars for use in IPM programs [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%